Diagnóstico Nanda en neonatos en el Hospital Isidro Ayora de Loja - Barrezueta Carrillo, Angie Pamela (2019)
The use of NANDA diagnoses in neonates is important, because the nursing professional is the one who issues a clinical judgment on real or potential health problems, and then plans sick care, since newborns require a series of more care or less routine; therefore a careful assessment of its general condition, must follow a strict protocol and ensure adequate surveillance by properly trained and qualified health personnel to provide comprehensive care. The purpose of the study was to determine the frequent NANDA diagnoses in neonates, is a qualitative, descriptive, cross-sectional and observational research, in the study 230 neonates who remained in maternal care in the area of Gynecology-Obstetrics of the General Hospital Isidro Ayora participated from Loja; for the assessment we used the fourteen needs of Virginia Henderson, obtaining the following results, the need to maintain body temperature within normal limits was the most affected presented in all neonates under study, followed by the need to learn with 110 neonates and the need to avoid environmental hazards and injure others with 85. In conclusion, the most frequent nursing diagnoses found were: Risk of temperature imbalance (00005) related to age extremes and inactivity, 221 newborns were presented, provision for improve the maternity process (00208) related to which mother shows link with the care of the baby with 84 newborns and ineffective breastfeeding (00104) related to the infant is unable to correctly take the mother's breast, manifested by reflex of suction of all the neonates in study 57 presented it. Keywords: neonate, Virginia Henderson needs, NANDA diagnostics.